Occupational Performance and its Correlation with Some of Anthropometric Variables for Sports Supervisors in the Directorates of Youth and Sports - Sawsan Hadoud Obeid Shaileh (Journal of Global Pharma Technology, 2016)
The study aimed to identify the relationship between the professional performance of the supervisors who are specialists in physical education and sports sciences with some anthropometric measurements in the directorates of youth and sports. The study also assumed that there is a statistical relation between the professional performance and some anthropometric variables in the sports supervisor in the youth and sports directorates. The descriptive approach was used in the style of correlative relationships to suit the nature of the research procedures. The sample was divided according to the age groups into two groups, ranging between 25-35 years and a second group ranging in age from 35-45 years. After the tests and measurements, Data and processed statistically to reach the results on which the following conclusions were reached:There is a significant correlation between the body mass index of overweight people with the variable length, while there is no relationship between BMI and the other variables investigated.There is a significant correlation between the variable height and weight for people with overweight.There is a significant correlation between the body mass index with the variable length and the variable occupational performance of people with normal weight.There is no correlation between the BMI and other variables investigated for people with normal weight.Keywords: Occupational performance, Anthropometric variables, Sports supervisors and youth.